TRENDS IN THE AD/HD EPIDEMIC IN NORWAY (1992–2011) - Hannås, Bjørg Mari (European Scientific Journal, ESJ, 2014)
At the heart of many debates about AD/HD in Norway lies the question whether too many or too few individuals are currently diagnosed with AD/HD or treated with AD/HD medications. Such debates often make use of figures that are not particularly significant when treated and handled in isolation from a meaningful context. The purpose of this article is to present a form of epidemiological picture of how the AD/HD concept has developed in Norway. The plan is to account for relevant figures, concepts and tendencies, so that they can be applied, commented on and assessed in relation to various questions and relevant discussions. Distinctive trends in the development are discussed and analysed with the help of models and perspectives from relevant sociological theories. A main argument put forward is that the AD/HD epidemic is a part of an increased medicalisation in society in general.